A review of the synthesis, fabrication, and recent advances in mixed dimensional heterostructures for optoelectronic devices applications. (February 2023) - Ahmad, Waqas; Tareen, Ayesha Khan; Khan, Karim; Khan, Maaz; Khan, Qasim; Wang, Zhiming; Maqbool, Muhammad
Highlights: Various techniques of synthesis and fabrication of mixed dimensional heterostructures. Recent advances in 0D, 1D, 2D, and 3D nanomaterials and heterostructures. Structural, electronic, photonic, and optoelectronic properties of mixed dimensional heterostructures. Mixed dimensional heterostructures for optoelectronic devices fabrication. Improving the existing devices performance by using mixed dimensional heterostructures. Abstract: Low dimensional materials are promising candidates for the construction of electronic and optoelectronic devices owing to their novel electronic structure and exciting physiochemical properties. The combination of various nanomaterials with different dimensionalities develops mixed dimensional heterostructures (MDHs) that exhibit tremendous potential for a wide range of applications. For instance, zero-dimensional (0D) materials are suitable for achieving high charge carrier mobility in semiconducting devices, one-dimensional material (1D) have the ability for the development of nanoscale electronics, while layered materials such as two-dimensional (2D) materials possess outstanding electronic, magnetic and optical properties allow us to construct the vdWs heterostructures without their lattice mismatch. 2D materials, along with different dimensionalities MDHs, depict the desirable properties of their components such as enhancing the charge carrier mobilities, strong optical absorption, broadband spectrum response, suppressing the dark current, faster response as well as enhanced responsivity that are well applied to develop the next generation optoelectronic devices. Dedicated efforts have been made for the growth of efficient MDHs, their basic understanding, and mechanical assembly for electronics and optoelectronics. This review presents a brief introduction of low-dimensional materials along with conventional and new approaches for synthesis, followed by discussing materials processing in terms of fabrication protocols of MDHs i.e., vertical heterostructure and lateral heterostructures. Photophysical properties of the MDHs are also investigated and analysed thoroughly. The latest optoelectronic application of MDHs, and the outlook of current status, challenges and future prospects of low-dimensional materials and their heterostructures for potential applications are included in this review. Graphical abstract: Image, graphical abstract